Development of astromath game to enhance interest and understanding in addition and subtraction - Izza Della Nur Rizki; Budi Mulyono; Elsa Susanti; Zulkardi; Meryansumayeka; Putri Aisyah; Chyrza Adhea Salsabila; Rafika Sari (LINEAR: Journal of Mathematics Education, 2025)
Innovative and engaging learning media are needed to overcome elementary school students' low interest and difficulty in understanding basic math operations. Therefore, this study aims to develop and test the validity, practicality, and effectiveness of educational game-based math learning media in understanding basic math calculation operations called Astromath. This media is designed to assist elementary school students in understanding mathematical concepts more enjoyably and interactively. The research employed the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Two material experts validated with a result of 85.83% (very valid category) and two media experts with a result of 90% (very valid category). The practicality test was conducted on two teachers and four first-grade elementary school students. The results of the teachers' assessments showed an average score percentage of 84.37%, categorized as very practical. In comparison, the students' practicality test results obtained an average percentage of 91.1%, which also fell into the very practical category. Furthermore, the pre-test and post-test results demonstrated a significant increase in students' understanding after using Astromath. Therefore, Astromath is declared effective, practical, and suitable for use as an alternative interactive and enjoyable learning media in elementary schools.